Beyond the Enviro-toon. The Ecocritical Theme in contemporary Animated Series for TV and OTT Media Services - Bellano, Marco (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
In 2011, Robin Murray and Joseph Heumann proposed an ecocritical reading of US animated production, further focusing on the definition of enviro-toon. It is a category that frames the dominant narrative models in US animation, introduced in 2004 by Jaime Weinman to distinguish superficially moralistic products from those animated works where, although the ecological theme is central, easy schematisations are not used (where ‘good’ would coincide with nature conservation, and ‘evil’ with pollution and the like), but a complex stratification of perspectives is created, and conclusions remain open. These are what, in 2012, Deidre Pike more precisely identified as dialogical enviro-toons. In the contemporary panorama of animation, though, the fictional serial products distributed by OTT media services seem to be implementing new discursive strategies about ecocritical issues, which are in turn also influencing TV serial animation. The ecological topic is often not the main force driving the narrative, but just one major thread within a more complex thematic texture. This is especially evident in the so-called “adult”-targeted animation, a marketing label introduced since the early 2000s in Western animation (for example by the night programming of Cartoon Network, called Adult Swim) to differentiate the serial products covering more sensible themes, like violence or sensuality, from the “regular” ones, supposedly targeted to children. While this labelling unfortunately perpetuates longstanding stereotypes about the perception of animation in the Western audience, the exploration of the so-called “adult” audience has fostered the development of series with a complex writing and a matching refined design and visual research. Among the series that cleverly embed ecocritical issues in their narratives, without being literal enviro-toons, are the Adult Swim Primal (2019-present), by Genndy Tartakovsky, as well as several episodes of Love, Death & Robots (2019-present), based on a strong critical interplay between thematic content and visual style. T he article analyses these series, to discuss how they challenge and expand the notion of enviro-toon.